The efficiency of reweighted minimum vector variance - Ali, Hazlina; Syed Yahaya, Sharipah Soaad; Omar, Zurni (2014)
Minimum vector variance (MVV) is a new robust estimator which possesses the good properties as in minimum covariance determinant (MCD), but with better computational efficiency.However, the highly robust affine equivariant estimators with the best breakdown point commonly have to compensate with low statistical efficiency.Hence, to increase the efficiency while retaining the highest breakdown point, we proceed to improve the MVV estimators in the context of statistical efficiency via reweighted version (RMVV).Interestingly, the reweighted scheme was able to maintain the breakdown point of 0.5 and attained higher efficiency at the normal distribution.